2019
DOI: 10.1039/c9nj02344e
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-doped fluorescent graphene nanosheets as visible-light-driven photocatalysts for dye degradation and selective sensing of ascorbic acid

Abstract: Facile synthesis of water soluble fluorescent N-doped graphene nanosheets for multifunctional applications in photocatalysis and sensing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 65 publications
0
26
0
Order By: Relevance
“…Graphene aerogel, synthesized from crude biomass, has been proposed to be an ecofriendly cell growth promoter and a highly efficient adsorbent for histamine, which is a food toxicant, removal from red wine [73]. Das et al used nitrogen-doped soluble graphene nanosheets as multifunctional materials for photocatalytic, sensing, and adsorption applications [74]. Moreover, Sulaymon et al reported that dead and live anaerobic biomass could be used for biosorption of Pb (II) ions from synthetic wastewater, and the uptake capacity was 51.56 mg g −1 [75].…”
Section: Discussionmentioning
confidence: 99%
“…Graphene aerogel, synthesized from crude biomass, has been proposed to be an ecofriendly cell growth promoter and a highly efficient adsorbent for histamine, which is a food toxicant, removal from red wine [73]. Das et al used nitrogen-doped soluble graphene nanosheets as multifunctional materials for photocatalytic, sensing, and adsorption applications [74]. Moreover, Sulaymon et al reported that dead and live anaerobic biomass could be used for biosorption of Pb (II) ions from synthetic wastewater, and the uptake capacity was 51.56 mg g −1 [75].…”
Section: Discussionmentioning
confidence: 99%
“…The photocatalytic activity of the nanoparticles was explored against MB dye and for this sample 10% Co:CsPbCl 3 was tested because of its superior structural and morphological properties. The photocatalytic experiments were carried out in a self made photocatalytic reactor reported in other publications 35 , 36 . The photocatalytic activity of the nanostructures was demonstrated under visible light illumination.…”
Section: Photo Catalytic Activitymentioning
confidence: 99%
“…This indicates that there were characteristic absorption peaks of inorganic substance compounds in the hybrid materials. The peak at 1120.12 cm -1 was the -C-C stretching vibration, the peak at 1349.02 cm -1 corresponded to the -C-N stretching vibration, the peak at 1625.79 cm -1 was the -C = O stretching vibration of the amide group, and the broad peak at 3200–3700 cm -1 corresponded to the stretching vibration of amino -NH 2 [ 63 , 64 ]. The characteristic peak of Zr-O-Zr, and the stretching vibration of -C-C, -C-N, -C = O, -NH 2 shifted marginally after the reaction.…”
Section: Resultsmentioning
confidence: 99%